2014
DOI: 10.7314/apjcp.2014.15.4.1751
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlations among Histopathological Parameters, Ki-67 Proliferation Index and Prognosis in Pheochromocytoma Patients

Abstract: Background: In this study prognostic correlations of histopathologic parameters and the Ki-67 proliferation index and as well as the diagnostic value of immunohistochemical markers in pheochromocytomas were evaluated. Materials and Methods: A total of 22 patients diagnosed with a pheochromocytoma between 2000-2010 in Izmir Katip Celebi University Ataturk Training and Research Hospital were included. Diagnostic value of the PASS scoring system, and prognostic correlations of histopathologic parameters and Ki-67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
(35 reference statements)
0
12
1
Order By: Relevance
“…The PASS was not originally developed for PGLs and, therefore, there is some uncertainty in applying the components of the PASS to these tumours. The clinical features and histopathological characteristics are, however, similar for PCCs and PGLs (31).…”
Section: Discussionmentioning
confidence: 89%
“…The PASS was not originally developed for PGLs and, therefore, there is some uncertainty in applying the components of the PASS to these tumours. The clinical features and histopathological characteristics are, however, similar for PCCs and PGLs (31).…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, our case of benign pheochromocytoma showed an extremely high level of cell proliferation potential, with a PI of 9.7 %. The relationships between cell proliferation and pathological characteristics including hormone secretion, tumor size, and symptoms in benign pheochromocytoma are not fully understood, although PI was reported to be significantly associated with capsule invasion of pheochromocytoma [ 24 ]. The relationship between the aggressiveness of PMC and cell proliferation is unknown, as this is the first report on cell proliferation in PMC.…”
Section: Discussionmentioning
confidence: 99%
“…Although differences were not documented in dogs, in humans with pheochromocytoma it has been shown that capsular invasion is associated with higher proliferation rate of tumor cells based on Ki-67. 18 Also, there were no differences for PASS and the immunohistochemical markers between young and old dogs. It is interesting to note that for pheochromocytomas a better outcome has been previously shown in younger dogs, 11 while in the present investigation age was not different between survivors and non-survivors.…”
Section: Discussionmentioning
confidence: 83%
“…6 Similarly to PASS, also some of the listed immunohistochemical markers, such as Ki-67, p53, BCL-2 and c-erbB-2, have not been invariably associated with a malignant course in humans with pheochromocytoma. 7,18,21 Alternatively, the lack of association between PASS or immunohistochemical markers and survival is explained be the relatively low number of dogs included in this study; the limited number may have decreased the chance to detect significant differences. Finally, it is worth mentioning that in humans with pheochromocytoma an important outcome predictor is represented by the presence of distant metastasis or their development during follow-up; metastasis can occur 5 years, or longer, after surgery.…”
Section: Discussionmentioning
confidence: 97%